Penerapan Metode Asuhan Keperawatan Primary Care dengan Rekam Medis Elektronik terhadap Kualitas Asuhan Keperawatan dan Kepuasan Pasien - Hutagalung, Myhrna Rosany; Inayah, Iin; Irianto, Gunawan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to identify the impact of implementing primary care with electronic medical records (EMR) on the quality of nursing care and patient satisfaction. The study used a retrospective design with secondary data from the Quality Department of Rumah Sakit Advent Bandung, with a sample of 150 inpatients selected through simple random sampling. Univariate analysis used the frequency distribution, and bivariate analysis used the Wilcoxon signed rank test. The results showed that before the implementation of primary care with EMR, 92.7% of nurses provided good-quality nursing care, and 72.7% of patients were satisfied with the services. After the implementation, 98.0% of nurses provided good-quality nursing care, and 76% of patients were satisfied with the nursing services. There was a significant impact of implementing primary care with EMR on the quality of nursing care and patient satisfaction, with a p-value = 0.0001 (p<0.05). In Conclusion, there is a significant relationship between the implementation of primary care with electronic medical records (EMR) on the quality of nursing care and patient satisfaction. Keywords: Electronic Medical Records (RME), Patient Satisfaction, Primary Care, Quality Of Nursing Care